Subcomandante Marcos : global rebel icon - Henck, Nick, 1971- (Black Rose Books, 2019)
"Henck explores Marcos's considerable accomplishments in four main fields: his role as spokesperson for the Zapatistas; his contribution to Latin American literature and a new political language for the Left; his work in making Mexico a more democratic, inclusive, and just nation; and his role as an inspirational international political icon."--